Inspired by batik sarung / Nur Aina Anuar - Anuar, Nur Aina (2022)
Batik Sarung is a large length of fabric, often wrapped around the waist, worn in Southeast Asia, South Asia, and on many Pacific islands. In Malaysia, the sarong is known as a kain. The fabric often has woven plaid or checkered patterns, or may be brightly colored by means of batik or ikat dyeing. Many modern sarongs have printed designs, often depicting animals or plants